THE REVERSE SELECTIVE BACTERIOSTATIC ACTION OF ACID FUCHSIN - Burke, Victor (The Rockefeller University Press, 1924)
1. The reverse selective action attributed to acid fuchsin can be explained on the basis of spore resistance. This action does not apply to the vegetative cells of Gram-positive spore bearers. It cannot be extended to include the Gram-negative spore bearers. 2. The selective action of acid fuchsin is that of an ordinary weak disinfectant and is not comparable to the selective action of the triphenylmethane dyes. 3. A lack of parallelism between the bactericidal and bacteriostatic action of acid fuchsin can be explained on the basis of spore resistance and it does not exist when spores are excluded. 4. Acid fuchsin is a weaker disinfectant than basic fuchsin for both Gram-negative and Gram-positive bacteria. The process of sulfonation by which acid fuchsin is made from basic fuchsin results in a reduction in the bactericidal action of the dye for Gram-negative and Gram-positive bacteria. 5. The most significant fact in the action of the dyes on bacteria is the toxic effect of the triphenylmethane dyes on Gram-positive spore-bearing organisms.